2014
DOI: 10.26719/2014.20.7.442
|View full text |Cite
|
Sign up to set email alerts
|

Case management of childhood tuberculosis in children's hospitals in Khartoum

Abstract: No published information is available on the case management of childhood tuberculosis (TB) in Sudan. The aim of this study was to describe the case management of childhood TB in 4 children's hospitals in Khartoum State, Sudan. Data on 467 children aged 0-14 years registered in 2009 were collected from patient records; 52.9% males and 53.0% aged 5-14 years. Most cases were registered as new cases (89.5%) and most had pulmonary TB (72.4%). Of all cases, 31.0% had sputum smear microscopy done, 35.8% had X-ray an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Again some clinician did not follow the childhood tuberculosis diagnosis organogram. Therefore, in this study, the size of the extra-pulmonary case were 678 (62.4%) which is consistent with a study finding of Addis Ababa 52.8% [5, 24].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Again some clinician did not follow the childhood tuberculosis diagnosis organogram. Therefore, in this study, the size of the extra-pulmonary case were 678 (62.4%) which is consistent with a study finding of Addis Ababa 52.8% [5, 24].…”
Section: Discussionsupporting
confidence: 92%
“…In this study among total cases who have treatment outcome records 35 (4.2%) children were died and it is higher than retrospective study done in Addis Ababa indicates 2% (5)and study report from Sidama 3% [21]. But, similar with the study done in Sudan 4.3% [24]. This high rate of death could be the region had high magnitude of child under nutrition which is 33% of children were underweight and 11.6% were wasted [27].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Despite these difficulties, 70% of patients completed their treatment at UCK; this rate was higher than that reported in Botswana [ 36 ] or Malawi [ 35 ] but lower than that in other studies in Africa that showed higher treatment success rates [ 34 , 44 ]. In fact, 10.8% of our patients failed defaulted, or died, suggesting poor case management and an inadequate control program for childhood TB.…”
Section: Discussionmentioning
confidence: 60%